Analysis Of Smart Monitoring Condition Room Planning Of British Education Center Medan File Room Using Blynk Software - Aji Prayogo; Solly Aryza; Amani Darma Tarigan (Sean Institute, 2024)
This study discusses the analysis of the planning of a smart monitoring system for the condition room for the file room at the British Education Centre Medan using Blynk software. This system is designed to monitor room conditions in real time, including temperature, humidity, and security, with the aim of maintaining the quality of file storage and preventing damage due to uncontrolled environmental changes. Blynk is used as the main platform for hardware integration with mobile applications, allowing users to access and monitor room conditions remotely via smartphone devices. The system planning process involves selecting appropriate sensors, designing communication networks, and setting up interfaces on the Blynk application. The results of this planning analysis indicate that the implementation of an IoT-based monitoring system such as Blynk can improve efficiency and accuracy in monitoring room conditions, as well as provide direct notification to users if an abnormal condition occurs. Thus, this system can help maintain the security and quality of files stored in the room, as well as offer a more effective and modern solution in managing the file room.